2008
DOI: 10.4049/jimmunol.180.6.3729
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RNA Sequence Motifs Stimulating Sequence-Specific TLR8-Dependent Immune Responses

Abstract: The TLRs 7, 8, and 9 stimulate innate immune responses upon recognizing pathogen nucleic acids. U-rich RNA sequences were recently discovered that stimulate human TLR7/8-mediated or murine TLR7-mediated immune effects. In this study we identified single-stranded RNA sequences containing defined sequence motifs that either preferentially activate human TLR8-mediated as opposed to TLR7- or TLR7/8-mediated immune responses. The identified TLR8 RNA motifs signal via TLR8 and fail to induce IFN-α from TLR7-expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
261
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(280 citation statements)
references
References 54 publications
10
261
0
Order By: Relevance
“…Furthermore, speciesspecific variation in PolyU-mediated TLR8 activation has previously been described in immune cells (40,41). PolyU activated TLR8 in human and bovine leukocytes but failed to activate TLR8 on immune cells in mice and rats (39). Our findings are consistent with these data.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, speciesspecific variation in PolyU-mediated TLR8 activation has previously been described in immune cells (40,41). PolyU activated TLR8 in human and bovine leukocytes but failed to activate TLR8 on immune cells in mice and rats (39). Our findings are consistent with these data.…”
Section: Discussionsupporting
confidence: 83%
“…preferentially activate TLR8 and not TLR7 (39). Although less is known about TLR8, it is highly homologous to TLR7 and similarly recognizes single-stranded RNA.…”
Section: Discussionmentioning
confidence: 99%
“…(27). It has been reported that 29-O methylation of any nucleotide in ssRNA can abrogate its immunostimulatory effect (28) and, as a result of higher receptor affinity, can compete with other immunostimulatory ssRNAs for TLR7 binding (29).…”
Section: Mapping Of Endosomal Rna Sensors Highlights the Role Of Tlr7mentioning
confidence: 99%
“…TLR7 is expressed in human B cells and plasmacytoid dendritic cells (4) and TLR8 is expressed in human monocytes and myeloid dendritic cells (8,9). Wide use of synthetic RNA as agonists of TLR7 and TLR8 has been hampered by their susceptibility to nuclease degradation (10)(11)(12), and lipid carriers have been needed for in vitro and in vivo studies (8,(11)(12)(13). We have reported a novel class of synthetic oligoribonucleotides, referred to as stabilized immune-modulatory RNA (SIMRA) compounds (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%